Extração do óleo da semente do melão cantaloupe - Teixeira, Roberta Kerolayne Campielo dos Santos (Universidade Federal Rural do Semi-Árido, 2019)
Vegetable oils have a vast technological potential in several areas of the chemical, food and pharmaceutical industry. The Northeast Region stands out as the main melon producer in Brazil, however the seeds are discarded as residue although they present nutritional qualities and the possibility of utilizing the oil. In this study, different extraction techniques (Soxhlet and ultrasound) and different operational conditions were investigated in order to quantify the oil content in the cantaloupe melon seeds (Cucumis melo var. Cantalupensis). The maximum yield found was 19.70% for ultrasonic extraction using hexane as the solvent.
Artigo
Keywords: Melão cantaloupe; Extração; Hexano; Soxhlet; Ultrassom; Melon cantaloupe; Extraction; Hexane; Soxhlet; Ultrasound; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA